Projeto - Objetos que contam história - Chaves, Ana Lúcia Ferreira; Okazaki, Maria Silva Guimarães; Domingos, Maria Aparecida; Lima, Eliene Xavier de; Quadros, Izabel Cristina Rezende de (REVISTA PROGRAMA A UNIÃO FAZ A VIDA_____________________________________________________________________________________________________________, 2021)
>>> VER PDF